Design of a Vehicle Parking Management Information System in Tanjung Duren Central Park Area West Jakarta: Author's Country: Indonesia (Information System; Universitas Buana Perjuangan Karawang, 2025)
Tanjung Duren Parking is a parking lot whose operational activities still use a manual system, so that parking officers often experience problems such as incorrectly calculating the total parking fee or incorrectly recording incoming and outgoing vehicles, which results in parking revenue anomalies and inaccurate parking space availability data. Therefore, in this research, a parking vehicle management information system was designed as a solution to existing problems. This information system was designed using the system development life cycle (SDLC) method and approach. Based on the results of research that has been carried out, it is known that the information system that has been designed is effective to implement because it is able to solve existing problems such as automatically calculating parking rates and recording vehicles both when entering and leaving